Sealife Travel & Tour Online Booking System / Nurul Athirah Ahmad Nazri - Ahmad Nazri, Nurul Athirah (2020)
Sealife Travel & Tour Online Booking System is a platform that able the customer to make the booking through online. As we know, nowdays people are searching for something that can ease their daily life. The use of technology also increasing day by day. The customer can save their time by doing online booking. They do nor have to walk in into the company. Moreover, the customer can make their online booking and online transaction by using this system. They can transfer the amount to the company directly without having to pay in cash. The use of online transacrtion The user for this system is the customer, admin and the manager. Each user have their function. This system also can ease the manager and the admin. The admin can directly add the package into the system and the customer can view the packages and information. The manager cana view the ales report. This can help them to plan a strategy to increase the company profit.